El Carlos Marx de Roque Dalton (o sobre el Marx responsable “de la felicidad que sigue caminando”) - Retana, Camilo (2009)
This article demonstrates the existence of an autochthonous interpretation of classic Marxism in the poetry of Salvadorian author Roque Dalton. His poetry is therefore interpreted as a contribution to that Latin American thinking interested in creating a Marxism adapted to our characteristics.